Komposisi Fraksi Pasir dan Sifat Kimia Tanah Pada Areal Revegetasi Lahan Bekas Tambang Batubara - Ria Rachel Paranoan (Universitas Widya Gama Mahakam, 2019)
The purpose of this research were to determine the composition of sand fraction and chemical properties at revegetation area. The research was conducted from April to October 2019 . The mineralogical Compositions of sand fraction were analyzed using a Polarizing Microscope (PM) at the laboratory of Mineral BB Litbang SDLP, Bogor. The results showed that the composition of sand fractionof soil at revegetation area was dominatd by quartz,with small amounts of opaque, zircon,weathered mineral, rock fragment, and tourmaline.Chemical properties indicated that the soil at revegetation area showed pH from 6,05 to 6,49, had low content of cation exchange capacity in the whole layers, very high content of base saturation, very low to low organic carbon. Exchangeable K and Na are low in the whole layers, the moderate content of potential potassium. Both exchangeable Ca and Mg were lot to moderate. Potentioal P content in soil varies from moderate to high.Soil management in revegetation area should be focused on Maintaining soil fertility through application of liming, and fertilizers